2017
DOI: 10.1038/srep40403
|View full text |Cite
|
Sign up to set email alerts
|

Methionine residues around phosphorylation sites are preferentially oxidized in vivo under stress conditions

Abstract: Protein phosphorylation is one of the most prevalent and well-understood protein modifications. Oxidation of protein-bound methionine, which has been traditionally perceived as an inevitable damage derived from oxidative stress, is now emerging as another modification capable of regulating protein activity during stress conditions. However, the mechanism coupling oxidative signals to changes in protein function remains unknown. An appealing hypothesis is that methionine oxidation might serve as a rheostat to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 68 publications
1
60
0
2
Order By: Relevance
“…This isolated observation prompted us to test the hypothesis that reversible methionine oxidation might be used in a generalized way as a rheostat to control the phosphorylation of proximal phospho acceptors. To this end, we analyzed the co‐occurrence of these two types of PTMs (sulfoxidation and phosphorylation) within the human proteome . In that study we showed that as many as 98% of the proteins containing oxidized methionine after an oxidative insult were also phosphoproteins.…”
Section: Cross‐talk Between Methionine Sulfoxidation and O‐phosphorylmentioning
confidence: 88%
See 2 more Smart Citations
“…This isolated observation prompted us to test the hypothesis that reversible methionine oxidation might be used in a generalized way as a rheostat to control the phosphorylation of proximal phospho acceptors. To this end, we analyzed the co‐occurrence of these two types of PTMs (sulfoxidation and phosphorylation) within the human proteome . In that study we showed that as many as 98% of the proteins containing oxidized methionine after an oxidative insult were also phosphoproteins.…”
Section: Cross‐talk Between Methionine Sulfoxidation and O‐phosphorylmentioning
confidence: 88%
“…Furthermore, phosphoserine (pSer) and MetO sites cluster together in a statistically significant way when compared to Ser and Met. This proximity between modification sites could not be accounted for by their colocalization within unstructured regions because it was faithfully reproduced in a smaller sample of structured proteins . Overall, the results of that study strongly suggest that methionine sulfoxidation in the phosphorylation motifs it is not a random process directed by mass action, but on the contrary, it is a highly specific and selective process.…”
Section: Cross‐talk Between Methionine Sulfoxidation and O‐phosphorylmentioning
confidence: 99%
See 1 more Smart Citation
“…The only established pattern known to affect methionine reactivity is the interaction of its sulfur atom with the aromatic ring of tyrosine and other aromatic amino acids 37,38 , reducing its propensity to oxidation 39 . Additionally, a recent report provided a bioinformatics evidence that methionine oxidation is enriched in the proximity of phosphorylation sites 40 . Identification of methionines oxidized in vivo lags behind the research on cysteine oxidation.…”
Section: Oxidation Of Methionine: Where When and How?mentioning
confidence: 99%
“…3840 For example, a previous study showed that oxidized Met residues were located in closer proximity to phosphorylation sites than non-oxidized ones. 41 In addition, Met residues are often located in spatial proximity to aromatic rings, contributing to protein stability through the hydrophobic effect. 42 The oxidation of such Met residues can lead to conformational changes that result in the exposure of previously unexposed hydrophobic residues.…”
Section: Discussionmentioning
confidence: 99%